PENATAAN PENEMPATAN LOKASI PAPAN PETUNJUK JALAN DAN INFORMASI (SIGNAGE SYSTEM) - Geby Fathona; Abdul Hamid Hakim; Rizqiyah Safitri Juwito (LOSARI Jurnal Arsitektur, Kota dan Permukiman, 2020)
Bengkulu city Pantai panjang Nature park area (TWA) includes the National Tourism Development Zone (KPPN). The existence of Pantai panjang TWA in the middle of Bengkulu City is a special attraction for tourists. This study aims to achieve the main function of the Pantai panjang TWA area that is as a public space that should provide convenience for every tourist who is visiting. This research is focused on physical elements such as road signs and information. It was realized that the Pantai Panjang TWA area did not yet provide much convenience for tourists to get appropriate directions and information. Signage and information in the Pantai Panjang TWA area are expected to be a participatory communication medium based on the location of the arrangement and the suitability of the information The research method used is descriptive qualitative, quantitative and spatial (photo mapping) methods (Creswell, 2008), and in the form of literature studies, field observations, and interviews. The proper arrangement related to the placement of the points of the location of the road signs and information (signage system), it is expected that the information provided will be conveyed to tourists visiting the Pantai Panjang TWA area.